Magneto Optical Polarization Measurements using THz Polarization Modulation Spectroscopy - Stier, A. V.; George, D.; Markelz, A. G.; Cerne, J. (2011 36th International Conference on Infrared, Millimeter, and Terahertz Waves, 2011)
We report a new broad band technique for rapidly measuring the complex Faraday and Kerr rotations in materials such as topological insulators and graphene, combining the distinct advantages of THz time domain spectroscopy and polarization modulation techniques. The performance of the system is demonstrated using GaAs two dimensional electron gas in a magnetic field.